Addressing Health Equity Leadership in Action: A Pilot Partnership Experience - Atwater, Sierra; Marshall, Emily Hatheway; Kinamon, Tori; Doty, Joe (Journal of Education and Training, 2023)
Due to systemic injustices, people of color and other underserved groups experience higher rates of illness and death across a multitude of health conditions. This leaves a large group of individuals medically vulnerable, limiting the health of the nation. Achieving health equity requires intentional, mindful, action from leaders, physicians, community partners, business executives, and all those impacted by inequity. As part of a collaboration between the Feagin Leadership Program (FLP) at the Duke University School of Medicine and the Augustus A. White III Institute for Healthcare Equity (AAWI) in Boston, we orchestrated a Health Equity Leadership forum. The resulting discussion brought forth several key actionable solutions to improving health equity, specifically in the field of medical education. It is our hope that by shedding light on this pilot collaborative effort and sharing the actionable outputs from the forum, we can inspire and empower intentional leaders to utilize this model to make changes towards equitable healthcare today.